Neural substrates underlying fear‐evoked freezing: the periaqueductal grey–cerebellar link. (22nd April 2014) - Koutsikou, Stella; Crook, Jonathan J.; Earl, Emma V.; Leith, J. Lianne; Watson, Thomas C.; Lumb, Bridget M.; Apps, Richard
Abstract : Key points: At the heart of the brain circuitry underlying fear behaviour is the periaqueductal grey (PAG). We address an important gap in understanding regarding the neural pathways and mechanisms that link the PAG to distinct patterns of motor response associated with survival behaviours. We identify a highly localised part of the cerebellum (lateral vermal lobule VIII, pyramis) as a key supraspinal node within a chain of connections that links the PAG to the spinal cord to elicit fear‐evoked freezing behaviour. Expression of fear‐evoked freezing behaviour, both conditioned and innate, is dependent on cerebellar pyramis neural input–output pathways. We also address an important controversy in the literature, namely whether or not ventrolateral PAG (vlPAG) increases muscle tone. We provide evidence that activation of the vlPAG causes an increase in α‐motoneurone excitability, consistent with a role in generating muscle tone associated with fear‐evoked freezing. Abstract: The central neural pathways involved in fear‐evoked behaviour are highly conserved across mammalian species, and there is a consensus that understanding them is a fundamental step towards developing effective treatments for emotional disorders in man. The ventrolateral periaqueductal grey (vlPAG) has a well‐established role in fear‐evoked freezing behaviour. The neural pathways underlying autonomic and sensory consequences of vlPAG activation in fearful situations are well understood, but much less is known about the pathways that link vlPAG activity to distinct fear‐evoked motor patterns essential for survival. In adult rats, we have identified a pathway linking the vlPAG to cerebellar cortex, which terminates as climbing fibres in lateral vermal lobule VIII (pyramis). Lesion of pyramis input–output pathways disrupted innate and fear‐conditioned freezing behaviour. The disruption in freezing behaviour was strongly correlated to the reduction in the vlPAG‐induced facilitation of α‐motoneurone excitability observed after lesions of the pyramis. The increased excitability of α‐motoneurones during vlPAG activation may therefore drive the increase in muscle tone that underlies expression of freezing behaviour. By identifying the cerebellar pyramis as a critical component of the neural network subserving emotionally related freezing behaviour, the present study identifies novel neural pathways that link the PAG to fear‐evoked motor responses.